Open Innovations in Human Resource Management Practices in the Tanzania Public Service: Assessment of the Public Service Guiding Frameworks - Marijani, Ramadhani; Milanzi, Montunus C. (Journal of Policy and Leadership, 2022)
This article presents the open innovations status in human resource management practices within the Tanzania public service. The study focuses on open innovations in the Government of the United Republic of Tanzania, particularly from 1999. This was the period when the new policy on public service management and employment was crafted and adopted by the Government. The document review was conducted to identify open innovations that were anticipated and implemented within the public service. The results show that open innovation is constrained by the presence of uniform, less coordinated policies (and legislation) and inadequate pecuniary and non-pecuniary incentives to innovate. It is concluded that public sector institutions in Tanzania have to work together (non-symbiotic) to allow open innovations to take place within the public service. It is also recommended that public servants must be ready and flexible to utilize ideas and knowledge from outside that are relevant to their institutions. Similarly, public institutions should transmit their unused ideas and knowledge to other public institutions for use to improve the performance of their respective institutions. We recommend other researchers venture into researching open innovation in the context of digital governance transformation in the public service in Tanzania and or how open innovation may enhance co-design and co-delivery in the context of decentralization in Tanzania, specifically, the use of improved Opportunities and Obstacles to Development (OOD) tool.